GREEN ECONOMY: THEORETICAL FOUNDATIONS AND STRATEGIC PROSPECTS OF SUSTAINABLE DEVELOPMENT - Ulug’murodov Farhod Faxriddinovich,; Toshboyeva Sabrina, (TADQIQOTLAR, 2026)
ABSTRACT   This  article  is  aimed  at  analyzing  the  theoretical  foundations  of  the  green economy  concept,  systematically  examining  its  ecological,  economic,  and  social dimensions, and evaluating its impact on sustainable development strategies. The study employs  qualitative  methodology,  integrating  policy  documents  from  international organizations,  case  study  analysis,  and  multi-dimensional  assessment  methods. Primary  sources  selected  include  reports  from  the  United  Nations  Environment Programme (UNEP), the World Bank, the International Labour Organization (ILO), and current academic literature. The research results demonstrate that the transition to a green economy has the potential to create up to 24 million new jobs in the renewable energy  sector  and  could  add  trillions  of  dollars  in  additional  value  to  the  global economy by 2050. However,  this transition requires substantial initial investments, institutional  restructuring,  and  social  adaptation  mechanisms.  Key  challenges identified in the article include financial barriers, policy inconsistencies, and industrial sector  resistance  to  structural  change.  Proposed  solutions  include  carbon  pricing mechanisms, international financial cooperation, and just transition strategies.